Сутність стратегії підприємства та класифікація її видів - Довбня С. Б.; Папуша І. В. (НТУ "ДП", 2023)
Результати. Статтю присвячено дослідженню еволюції стратегії підприємства як економічної категорії та основного елемента стратегічного управління. Сформовано сучасне розуміння поняття «стратегія підприємства». Виявлено розбіжності щодо визначення й характеристики видів стратегій підприємства, способів її класифікації. Results. The article is devoted to the study of the evolution of the company's strategy as an economic category and the main element of strategic management. A modern understanding of the concept of «enterprise strategy» has been formed. Disagreements were revealed regarding the definition and characteristics of types of enterprise strategy, methods of its classification. An updated modern interpretation of the concept of «enterprise strategy» was formed, the main types of strategy at different hierarchical levels were characterized according to the ssence, functional features, expected outcomes, etc. A mechanism for forming the company’s strategic set is proposed, which involves implementation in a logical sequence of stages, which ensures the validity of the process of forming the company’s strategy.
The essence of enterprise strategy and classification of its types
Keywords: стратегія підприємства; класифікація стратегій; стратегічне управління; корпоративна стратегія; конкурентна стратегія; функціональні стратегії; операційна стратегія; механізм формування стратегії; enterprise strategy; classification of strategies; strategic management; corporate strategy; competitive strategy; functional strategies; operational strategy; strategy formation mechanism